한국 자연휴양림의 생물다양성 보전 기능을 고려한 산림OECM 등재 적합성 검토 - 정다인; Da In Jeong; 안종빈; Jong Bin An (한국산림과학회지, 2025)
생물다양성협약(CBD)에서 글로벌 생물다양성 프레임워크(K-M GBF)가 채택됨에 따라 전 지구의 30%를 보호지역 및 OECM으로 보전하는 2030 실천목표에 합의하였다. 이에 본 연구는 OECM 제도 도입 초기부터 유력한 후보지로 거론되어 온 국립자연휴양림을 대상으로 산림OECM 등재 확대를 위한 적합성 평가를 수행하였다. 연구대상은 국립자연휴양림 83개소이며, 국립수목원과 국립산림과학원(NIFoS-KNA, 2024)에서 개발한 산림OECM 평가기준을 준용하여 분석을 진행하였다. 연구 결과, 국립자연휴양림은 생태적 보전을 위한 최소한의 지리적 경계와 관리체계를 갖추고 있어 보호지역과의 중첩 여부, 거버넌스 관련 기준을 충족하는 것으로 나타났다. 그러나 제도적 목적이 휴양에 중점을 두고 있어 생물다양성 보전 관련 효용성과 형평성 항목에서 일부 한계가 확인되었다. 자연휴양림 83개소에 대한 개별평가 결과, 55개소가 산림OECM 등재 가능한 것으로 확인되었다. A등급 9개소, B등급 16개소, C등급 24개소, D등급 6개소로 분류되었으며, 산림OECM 등재 시 인접 보호지역과의 생태적 연결성 증진 및 국내 보호지역 확대에 기여할 수 있을 것으로 기대된다. 다만, 일부 정성적 평가항목에서 평가자의 주관이 개입되는 한계가 확인되었으며, 이에 대한 보완을 위해 명확한 판단 기준과 구체적인 평가 방법의 제시가 필요하다. 또한 등재 이후 제도의 실효성 확보를 위해 법적·제도적 기반 마련 및 관리체계 구축이 병행되어야 한다. 본 연구는 국립자연휴양림의 공간적, 제도적 특성을 기반으로 산림OECM 등재 적합성을 종합적으로 평가하고, 향후 지역 수준(site-level)의 심층 평가와 등재 확대를 위한 기초자료를 제시하였다는 데 의의가 있다. With the adoption of the Global Biodiversity Framework (Korea-Montreal GBF) at the Convention on Biological Diversity (CBD), the 2030 Action Plan stipulates an agreement to conserve 30% of the planet as protected areas and Other Effective Area-Based Conservation Measure (OECM). This study conducted an assessment of the suitability of expanding the Forest OECM designation to national natural recreation forests, which have been considered potential candidates since the introduction of the OECM system. Analysis focused on 83 national natural recreation forests according to the Forest OECM evaluation criteria developed by the Korea Forest Service and the National Academy of Forest Sciences in 2024. The results demonstrated that national recreation forests possess minimal geographical boundaries and insufficient management systems for ecological conservation, thus fulfilling the criteria for overlap with protected areas and governance. However, the study identified a number of limitations in utility and equity categories related to biodiversity conservation, as the institutional objective centers on forest recreation. The study confirmed that 55 national natural recreation forests were eligible for OECM registration. They were categorized into four grades: 9, 16, 24, and 6 sites were classified Grades A-D, respectively. Their designation could contribute to the enhancement of ecological connectivity with neighboring protected areas and the expansion of protected areas in Korea. The study also observed limitations in the subjectivity of evaluators in relation to qualitative assessment items. Thus, providing clear judgment criteria and specific assessment methods is necessary to compensate for these limitations. In addition, a legal and institutional framework and management system should be established to ensure the effectiveness of the post-designation system. The significance of this study lies in its comprehensive evaluation of the suitability of national natural recreation forests for OECM designation based on spatial and institutional characteristics and recommendation of the basis for in-depth site-level evaluation and expansion of the listing in the future.